Efek Ekstrak Etanol Daun Gedi Merah (Abelmoschus manihot (L.) Medik) terhadap Kadar TNF-Alfa Jaringan dan Diameter Lumen Aorta Tikus Model Diabetes Melitus - Nanda Yunita Ayu Fitriyah; Juliet Tangka; Yeni Amalia; Yudi Purnomo (Jurnal Kedokteran Komunitas, 2020)
Introduction : Chronic hyperglycemia increase ROS production and risk of diabetic macroangopathy complications. Abelmoschus manihot (L.) Medik has potential as an antidiabetic and anti-inflammatory, but research on Abelmoschus manihot (L.) Medik inhibiting elevated levels of TNF-α tissue and aortic lumen diameter that contribute to complications has not been widely reported. This research aimed to determine the effect of ethanol extract Abelmoschus manihot (L.) Medik by observing the level of TNF-α tissue and aortic lumen diameter in diabetic rats.Methods : This study use 4-6-weeks-old Sprague dawley male rats which divided into normal group, diabetes mellitus group, and ethanol extracts of gedi merah leaves doses I (200 mg/kgBW), II (400 mg/ kgBW), and III (800 mg/kg BW) (n = 5 rats). The rats were induced HFFD and 25 mg/kgBW of STZ injection i.p with multiple dose. The rats were administrated orally EEDGM for 4 weeks. The level of TNF-Alfa aortic tissue was measured using microplate reader λ = 450 nm, while the aortic lumen diameter was examined using a trinocular microscope at 40x magnification. Statistical analysis using One Way ANOVA and LSD test (p <0.05).Results : EEDGM dose II and III inhibit the increase levels of TNF-α rat aortic tissue. EEDGM doses I, II, and III were not significant inhibit the decrease of aortic lumen diameter compared to KDM (p> 0.05). DTLF and STZ induction increases tissue TNF-α levels and decreases the aortic lumen diameter.Conclusion : Ethanolic extract of Abelmoschus manihot (L.) Medik could inhibit the increase in TNF-α levels of aortic tissue and did not significant inhibit the decrease of aortic lumen diameter.Keywords : High fat diet, high fructose diet, streptozotocin, diabetes, inflammation